2016
DOI: 10.1002/pits.21928
|View full text |Cite
|
Sign up to set email alerts
|

Manualization, Feasibility, and Effectiveness of the School‐based Social Competence Intervention for Adolescents (Sci‐A)

Abstract: Despite the movement toward identification of evidence‐based practices (EBPs), there is a discrepancy in the availability of school‐based EBPs targeting the unique needs of students with high functioning forms of autism and related social needs. Based on calls for systematic intervention development and evaluation processes, the current study describes the manualization, feasibility, and effectiveness testing of the school‐based Social Competence Intervention for Adolescents (SCI‐A) curriculum. School personne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 43 publications
4
32
0
2
Order By: Relevance
“…Previous research [ 22 , 23 ] supports the effectiveness of the SCI-A program in improvements in parent reports of social competence behaviors and characteristics of adolescents with HFA. In addition, pre- to postintervention improvements in EF as assessed by measures such as the Behavior Rating Inventory of Executive Function (BRIEF; [ 58 ]) and the Test of Problem Solving-3 (TOPS-3; [ 59 ]) were also found in these studies.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Previous research [ 22 , 23 ] supports the effectiveness of the SCI-A program in improvements in parent reports of social competence behaviors and characteristics of adolescents with HFA. In addition, pre- to postintervention improvements in EF as assessed by measures such as the Behavior Rating Inventory of Executive Function (BRIEF; [ 58 ]) and the Test of Problem Solving-3 (TOPS-3; [ 59 ]) were also found in these studies.…”
Section: Introductionmentioning
confidence: 84%
“…The Social Competence Intervention-Adolescent (SCI-A; [ 22 , 23 ]) is based on cognitive behavioral intervention and applied behavior analytic principles and targets EF, theory of mind, and emotion recognition as key constructs in addressing social competence impairments. Although other researchers have investigated the potential role of EF, theory of mind, and emotion recognition in existing intervention programs [ 21 ], SCI-A was developed specifically with these target constructs in mind.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Children also demonstrated significant improvements in their abilities to follow directions, transition easily, and to avoid getting stuck, as well as in social reciprocity, though this improvement also occurred for those in the control group. Similarly, Stichter, Herzog, Owens, and Malugen [] report positive outcomes associated with their school‐based Social Competence Intervention for Adolescents (SCI‐A) utilized with children with high‐functioning autism and similar social challenges, including improved shifting, emotional control, working memory, planning and organization, and monitoring, as rated by teachers and parents, as well as improved social responsiveness. Finally, Hilton et al [] describe a small‐scale light and sound speed‐based exergaming intervention, the Makota arena training intervention (Makoto USA, n.d.), which was associated with improvements in metacognition among children with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been found that the estimates of parents and teachers of change and planning/organization of the BRIEF are normalized with the implementation of a cognitive-behavioral intervention in the school, which focused on flexibility and planning (Kenworthy et al, 2014). In the same line, very promising results have been reported, emotional control, working memory, planning and monitoring with children with high functioning autism with a program in the school for the development of social competence in adolescents (Stichter, Herzog, Owens, & Malugen, 2016). To our knowledge the only work that has studied the impact of executive function training on ASD+ADHD found improvement in attention, impulsivity sympstoms and academic achievement in children and adolescents with ASD and comorbid ADHD (Weckstein, Weckstein, Parker, & Westerman, 2017).…”
Section: Resultsmentioning
confidence: 84%